2020
DOI: 10.1016/j.jaip.2019.10.017
|View full text |Cite|
|
Sign up to set email alerts
|

Phenotyping Occupational Asthma Caused by Acrylates in a Multicenter Cohort Study

Abstract: Background While acrylates are well-known skin sensitisers, they are not classified as respiratory sensitisers although several cases of acrylate-induced occupational asthma (OA) have been reported.Objectives The aim of this study was to evaluate the characteristics of acrylate-induced OA in a large series of cases and compare those with OA induced by other low-molecular-weight (LMW) agents.Methods Jobs and exposures, clinical and functional characteristics, and markers of airway Parts per billion QSAR:Quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 35 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…Isolated late reactions after exposure to diisocyanates are particularly well described [ 33 ]. In contrast, acrylates typically cause exposure-congruent symptoms, initially with rhinitis, conjunctivitis and urticaria [ 37 ]. However, even with diisocyanates, a reaction beginning later than 2 hours after the end of exposure is extremely rare [ 33 ].…”
Section: Evaluation and Interpretation Of The Test Resultsmentioning
confidence: 99%
“…Isolated late reactions after exposure to diisocyanates are particularly well described [ 33 ]. In contrast, acrylates typically cause exposure-congruent symptoms, initially with rhinitis, conjunctivitis and urticaria [ 37 ]. However, even with diisocyanates, a reaction beginning later than 2 hours after the end of exposure is extremely rare [ 33 ].…”
Section: Evaluation and Interpretation Of The Test Resultsmentioning
confidence: 99%
“…A Finnish study found that over 60% of occupational asthma and more that 20% of occupational rhinitis was associated with methacrylate materials in dental personnel 33 . In addition, further studies reinforce that daily methacrylate use has been associated with adult‐onset asthma, rhinitis, and conjunctivitis in dental personnel 32,35,37,38,76 with a reported prevalence estimate ranging from 1.3% to 14% 31 . Moreover, prevalence studies suggest a possible increasing trend with methacrylate sensitivity with estimates ranging from 1.3% to 25% in dental workers 18,31,46,77 .…”
Section: Respiratory Issuesmentioning
confidence: 94%
“…This inflammation leads to episodes repeated, particularly at night or early morning, lead to airway lightness and the coughing of susceptible people. The incidents usually involve significant but unpredictable airflow barriers, often reversible or therapeutic spontaneously [19,20]. The inflammation also raises the current bronchial hyperreactive to a variety of stimuli.…”
Section: Introductionmentioning
confidence: 99%